2013
DOI: 10.1155/2013/783519
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Silybin against Lasalocid Cytotoxic Exposure on Chicken and Rat Cell Lines

Abstract: Lasalocid, an ionophore coccidiostat, extensive use implies a risk of toxicological impacts. Protective effects of silybin, a herbal compound of Silybum marianum, are reported elsewhere. The aim of this study was to compare effects of the combined use of lasalocid and silybin in chicken hepatoma cells (LMH) and rat myoblasts (L6) cell lines cultures. The cytoprotective effect resulting from an interaction of both pharmaceuticals was measured with the help of MTT reduction and, coomassie brilliant blue binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
(38 reference statements)
1
5
0
Order By: Relevance
“…1,17 Hence, we evalauted the cytotoxicity of TCDWF on the progenitor stem cells as a measure of caspase elevation 36 and LDH release. 37,38 TCDWF appeared to protect phase I (EPO-independent) cells (compared with the normal control and phase II cell cultures) although a moderate amount of caspase 3 activity was detected in these cells induced with 220 μg ml À1 , suggesting a possible role of endogenous caspase 3 activity in early EPSC differentiation and HbF synthesis mediated by TCDWF, which is similar to the findings of Fernando and colleagues. 39 A different scenario was observed in phase II (EPO-dependent) erythroid progenitor cell cultures where TCDWF was added to the cells 5 days after the start of the culture; a significantly higher caspase 3 activity was observed, which was accompanied with significantly high levels of LDH release.…”
Section: Discussionsupporting
confidence: 86%
“…1,17 Hence, we evalauted the cytotoxicity of TCDWF on the progenitor stem cells as a measure of caspase elevation 36 and LDH release. 37,38 TCDWF appeared to protect phase I (EPO-independent) cells (compared with the normal control and phase II cell cultures) although a moderate amount of caspase 3 activity was detected in these cells induced with 220 μg ml À1 , suggesting a possible role of endogenous caspase 3 activity in early EPSC differentiation and HbF synthesis mediated by TCDWF, which is similar to the findings of Fernando and colleagues. 39 A different scenario was observed in phase II (EPO-dependent) erythroid progenitor cell cultures where TCDWF was added to the cells 5 days after the start of the culture; a significantly higher caspase 3 activity was observed, which was accompanied with significantly high levels of LDH release.…”
Section: Discussionsupporting
confidence: 86%
“…The term polyether carboxylic ionophore antibiotic refers to compounds with antimicrobial activity consisting of multiple ether moieties that, like beauvericin and enniatins, adopt a cyclic conformation where oxygen atoms are at the centre of a ‗doughnut-shaped' structure. Like beauvericin and enniatins, polyether carboxylic ionophores are cytotoxic in mammalian or chicken cell line cultures at concentrations in the low micromolar range (Radko et al, 2013). Thus, as observed with beauvericin and enniatins, polyether carboxylic ionophores are able to carry monovalent or divalent cations (K + , Na + , Ca 2+ , etc.)…”
Section: 7mentioning
confidence: 97%
“…The resulting changes in ion gradients and electrical potentials disrupt membrane functions and exert profound biological effects that were first recognised through their consequences on mitochondria resulting in the loss of energy production and adenosine triphosphate (ATP) synthesis (Estrada et al, 1974;Mitani et al, 1976;Wong et al, 1977;Pressman and Fahim, 1982). Like beauvericin and enniatins, polyether carboxylic ionophores are cytotoxic in mammalian or chicken cell line cultures at concentrations in the low micromolar range (Radko et al, 2013). These analogies ranging from the molecular structure to the common ion-translocating properties and comparable cellular toxicity may allow for the deduction of potential effects of beauvericin and enniatins in domestic animals from the well-known clinical and pathological changes elicited by polyether carboxylic ionophores.…”
Section: Toxicity Data On Structurally and Functionally Related Compo...mentioning
confidence: 99%
“…Studies have reported that lasalocid induces cytotoxic effects in liver cells by disturbing membrane ion transport and mitochondrial injury. Silybin exerts cytoprotective effects on HepG2 cells against the cytotoxic effects of lasalocid. , Zidovudine (AZT) is a nucleoside analogue that is commonly used to help control HIV infection. Moreover, it is also used with the antitubercular drug isoniazid (INH) due to the susceptibility of AIDS patients to tuberculosis.…”
Section: Detoxification Effectsmentioning
confidence: 99%